KELAYAKAN FINANSIAL PROYEK PEMBANGUNAN PERUMAHAN THE CITY INSIDE KOTA MALANG - Bagas Putranto, Djoko Trijanto, Medi Efendi (Prokons: Jurnal Teknik Sipil, 2018)
1.2 ha The City Inside is a housing construction project. This thesis is financial feasibility study to find out the house and the profit of the project through cash flows, Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (IP), and Benefit Cost Ratio (BCR) of types 47 and 65. Besides, the technical feasibility study discusses about the construction and implementation schedule of the project.The required data were of site plan, technical drawings, analysis of work unit price of Malang 2017. The financial feasibility results in IDR164.299.587,00 of type 47 and price of type 65; IDR339.734.500,00  operational cost; IDR188.830.077 for type 47 and IDR226.296.554,00 for type 65,  public facility; IDR94.591.130,00  cash inflow; IDR64.031.357.341,04  cash out flow; IDR46.492.361.358,33  NPV value meaning feasible to run ;interest IRR of 13.87% >12% meaning feasible and the 1.398 BCR meaning feasible;  feasible in 5.3 years PP. The sensitivity level at the rise and fall of 5% - 20% profit value, The sensitivity level at the rise and fall of 5% - 20% out cost value , The sensitivity level at the rise and fall of 5% - 20% of bank discount.The technical study results in orderly construction method  for type 47.  Keywords: financial, technical, feasibility, sensitivity analysis